2020
DOI: 10.5693/djo.01.2020.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Survey of musculoskeletal disorders among US ophthalmologists

Abstract: Purpose-To characterize the prevalence of work-related musculoskeletal disorders (MSD), symptoms, and risk factors among ophthalmologists.Methods-An online survey was distributed to ophthalmologist members of the Maryland Society of Eye Physicians and Surgeons. The survey consisted of 34 questions on respondent demographics, practice characteristics, pain, and effects of MSD on their practice patterns. Participants were excluded if they were not ophthalmologists or if they had MSD symptoms prior to the start o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…As observed in prior surveys, over-the-counter medications were a popular option, while surgeries and opioid use was seldom required. 1 , 3 , 5 , 6 , 9 The high frequency of postural changes and stretching aligns with prior claims that “working in the same position for long periods” and “working in awkward or cramped positions” contribute to ophthalmologists’ pain. 8 Furthermore, respondents in our study with greater spine-related disability were more likely to pursue practice modifications or attempt treatments.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…As observed in prior surveys, over-the-counter medications were a popular option, while surgeries and opioid use was seldom required. 1 , 3 , 5 , 6 , 9 The high frequency of postural changes and stretching aligns with prior claims that “working in the same position for long periods” and “working in awkward or cramped positions” contribute to ophthalmologists’ pain. 8 Furthermore, respondents in our study with greater spine-related disability were more likely to pursue practice modifications or attempt treatments.…”
Section: Discussionsupporting
confidence: 81%
“…Nearly half of the sample (48.1%) reported daily or weekly pain episodes, a rate that is within the range of prior reports. 6 , 9 Despite the high frequency of symptoms, our study found that there may be an underdiagnosis of MSK diseases in ophthalmologists, especially for shoulder pathologies. Slightly over half (54.2%) of those reporting shoulder pain had a corresponding diagnosis, versus 64.8% with back pain and 71.4% with neck pain.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations